2003
DOI: 10.1177/0891243202250851
|View full text |Cite
|
Sign up to set email alerts
|

Acid Violence And Medical Care In Bangladesh

Abstract: Acid attacks on women are increasing at alarming rates in Bangladesh, but the government has failed to provide medical care to the victims. Easily available sulfuric acid, which can mutilate a human face in moments, has emerged as a weapon used to disfigure a woman’s body. By the mid-1990s, activists had documented acid attacks, and urban protests were followed by demands for better medical care. I show how the interaction between local and international-level civil society organizations made international res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 2 publications
0
14
0
Order By: Relevance
“…When women do enter these spaces, they are tolerated only within very strict limits of movement, action, and dress and "transgressions" are often met with harsh retribution in the form of sexual and physical assaults. Anwary (2003) for instance discusses how the increase in acid violence against women in Bangladesh since the late 1980s may partly be a result of a reassertion of patriarchy in the face of perceived threats of female employment and independence. Similarly, it has been suggested that the postrevolution spate of sexual attacks on women in Egypt may be the result of a large-scale campaign from Egypt's security forces to undermine the political opposition.…”
Section: Strategies For Self-protectionmentioning
confidence: 99%
“…When women do enter these spaces, they are tolerated only within very strict limits of movement, action, and dress and "transgressions" are often met with harsh retribution in the form of sexual and physical assaults. Anwary (2003) for instance discusses how the increase in acid violence against women in Bangladesh since the late 1980s may partly be a result of a reassertion of patriarchy in the face of perceived threats of female employment and independence. Similarly, it has been suggested that the postrevolution spate of sexual attacks on women in Egypt may be the result of a large-scale campaign from Egypt's security forces to undermine the political opposition.…”
Section: Strategies For Self-protectionmentioning
confidence: 99%
“…Another major social problem is acid attacks on women, mainly due to refusal of marriage proposal and failure to give dowry to the husband. These attacks are increasing at alarming rates as government has failed to prosecute the attackers (Anwary, 2003). Drug addiction is gradually being increased (UNDCP 1997).…”
Section: Contextual Discussionmentioning
confidence: 99%
“…The expectation that women veil themselves in public has become more widespread in urban areas with the development of the garment sector and increasing numbers of women engaged in paid employment (Nazneen, 1996). Urban women realize more mobility through external employment (Amin & Pebley, 1994;Anwary, 2003). Women engaged in formal work outside the home are more likely to feel comfortable traveling unaccompanied to other public places such as a health clinic, market, or to visit their own families (Kabeer et al, 2011).…”
Section: Bangladesh As a Case Studymentioning
confidence: 99%